Membrane computing : 16th International Conference, CMC 2015, Valencia, Spain, August 17-21, 2015 : revised selected papers /: 16th International Conference, CMC 2015, Valencia, Spain, August 17-21, 2015 : revised selected papers. ([2015]) - Unknown
No abstract available